"الموافقات فی اصول الشریعہ": منہج اور خصوصیات (Al-Qamar, 2023)
Imām Abū Isḥāq al-Shaātibī, an Andalusian Sunni scholar of the Mālikī school, was a foundational figure in Usūl al-Fiqh (methodology of law). He passed away in 1388 (790 H) in Granada, Spain. Also known as Ibrāḥīm Ibn Mūsa Ibn Muhammad al-Shātibī al-Gharnāṭī. His works are essential readings in Usūl al-fiqh. For those engaged in ijtihād. “Al-Muwāfqāt fī Ūsūl al-Shariʼa” is a renowned work by Imām Shātibī that focuses on the principles of Islamic jurisprudence and their application to contemporary challenges, while addressing new issues that arise with changing times. In this context, Imām Shātibī employs innovative terminology to enhance the understanding of religious concepts, highlighting the significance of the objectives of Sharia and their adaptability through modern reforms.The book encompasses various dimensions of Islamic jurisprudence. Key points discussed in “Al-Muwāfqāt” include the exposition of hidden intricacies within the Hanafī school of thought, articulation of principles of legal objectives in the finest manner. The author emphasizes three central elements: discovering the true intent of legal rulings, ensuring practical application of these rulings, and considering the objectives behind them.Imām Shātibī introduces the concept of “Tawfiq Zahirī” as a way to reconcile differences among jurists with elegance. The author categorizes objectives into two types: objectives derived from the divine law and objectives related to human responsibilities.A prominent feature of “al-Muwāfaqāt” is its extensive utilization of Arabic language and contextual analysis of events. Imām Shātibī's meticulous examination of legal objectives, derivation of principles, and embrace of juristic guidelines is deemed crucial for achieving a comprehensive understanding of the objectives of Shāriʻa.
Keywords: Imām Abū Isḥāq al-Shātibī; Shariʻah; Usūl al-Fiqh; al-Muwāfaqāt adaptability; practical application; Reconciliation; Jurisprudential reasoning; Integration; Islamic jurisprudence